International Council for Standardisation in Haematology (ICSH) recommendations for collection of blood samples for coagulation testing. (7th June 2021) - Kitchen, Steve; Adcock, Dorothy M.; Dauer, Ray; Kristoffersen, Ann‐Helen; Lippi, Giuseppe; Mackie, Ian; Marlar, Richard A.; Nair, Sukesh
Abstract: This guidance document has been prepared on behalf of the International Council for Standardisation in Haematology (ICSH). The aim of the document is to provide guidance and recommendations for collection of blood samples for coagulation tests in clinical laboratories throughout the world. The following processes will be covered: ordering tests, sample collection tube and anticoagulant, patient preparation, sample collection device, venous stasis before sample collection, order of draw when different sample types need to be collected, sample labelling, blood‐to‐anticoagulant ratio (tube filling) and influence of haematocrit. The following areas are excluded from this document, but are included in an associated ICSH document addressing processing of samples for coagulation tests in clinical laboratories: sample transport and primary tube sample stability; centrifugation; interfering substances including haemolysis, icterus and lipaemia; secondary aliquots—transport and storage; and preanalytical variables for platelet function testing. The recommendations are based on published data in peer‐reviewed literature and expert opinion.